Mortalidad por COVID-19 y su relación con las búsquedas en internet sobre salud mental durante el primer año de pandemia. - Becerra-García, Juan Antonio; Sánchez-Gutiérrez, Teresa; Barbeito, Sara; Calvo, Ana (Revista de Psiquiatría y Salud Mental, 2023)
[Resumen no disponible]
COVID-19 mortality and its relationship with internet searches on mental health during the first year of pandemic
Keywords: COVID-19; mortalidad; internet; salud mental; pandemia; mortality; mental health; pandemic; JCR; Scopus